Optimisation of urea complexation by box-behnken design - Chin, Yoong Fei; Jumat Salimon,; Mamot Said, (Universiti Kebangsaan Malaysia, 2010)
Urea complexation is a method favoured by researchers to separate fatty acids based on molecular structure. In this study, effects of urea amount, crystallisation temperature and crystallisation time on the final products of urea complexation were examined. Box-Behnken Design (BBD) was employed to study the significance of these factors and the optimum conditions for the technique were predicted and verified. Results showed that urea-to-polyunsaturated fatty acid (PUFA) mole ratio and crystallisation temperature were two significant variables for enrichment of PUFA in non-urea complexing fraction (NUCF). In a 17-point experimental design, percentage of saturated fatty acid (SFA) was reduced almost entirely from initial 4.49%, monounsaturated fatty acid (MUFA) reduced from 57.02% to 41.32%, while PUFA increased from 33.49% to 53.87% in NUCF. Optimum condition for maximum PUFA and minimum SFA and MUFA contents was predicted at urea-to-PUFA mole ratio of 20, crystallisation temperature of –20 oC and crystallisation time of 29.67 h.